Neurone-specific enolase levels in pleural effusions in patients with rheumatoid arthritis. - Nyberg, P. (1996)
BACKGROUND: High pleural fluid levels of neurone-specific enolase (NSE) have been reported, not only in patients with small cell lung cancer but also in those with chronic inflammatory diseases. METHODS: NSE concentrations were determined in pleural fluid and serum from 342 patients with pleural effusions including 17 with rheumatoid arthritis. RESULTS: The median NSE concentration in pleural fluid was higher in rheumatoid effusions than in any other condition studied. The median pleural fluid:serum NSE ratio was highest in patients with rheumatoid arthritis (11.6) and about unity in all other diseases including small cell lung cancer (0.9). In patients with rheumatoid arthritis pleural fluid concentrations of NSE correlated inversely with pleural fluid glucose concentrations and the pH of the pleural fluid. CONCLUSIONS: A high pleural fluid:serum NSE ratio was found consistently in pleural effusions from patients with rheumatoid disease.